Agri-environmental governance and political systems in Central and Eastern Europe. (5th June 2006) - Sikor, Thomas
This paper presents an institutional analysis of agri-environmental governance in Central and Eastern Europe conducted by way of three case studies from Bulgaria, the Czech Republic and Poland. Building upon the theory on natural resource governance as developed by Ostrom and others, the analysis focuses on the linkages between agri-environmental governance and the political system. Its results suggest that the goods supplied by agriculture reflect the combined influence of four factors: excludability and scale as key features of the supplied good, and consolidation and centralisation as factors characterising the political system.